MICROGRAVITY AND SKELETAL DECONDITIONING: A NARRATIVE REVIEW OF BONE DENSITY LOSS AND EXERCISE COUNTERMEASURES IN ASTRONAUTS - Matuszek, Izabela; Badowska, Natalia; Wiśniewski, Bartosz; Pachnowska, Dominika; Pluta, Natalia; Nowak, Katarzyna Aleksandra; Rutkowska-Nowosielska, Alicja; Czekanow, Oliwia Nikola; Kania-Bonicka, Zofia; Demkow, Jerzy (International Journal of Innovative Technologies in Social Science, 2026)
Background: Microgravity uncouples skeletal remodelling — accelerating resorption and suppressing formation — causing BMD losses of 0.5–2%/month at weight-bearing sites, six-month ISS deficits are comparable to a decade of postmenopausal bone loss.Objective: To synthesise evidence on mechanisms, countermeasure efficacy, recovery, and gaps for exploration.Methods: Narrative review. PubMed/MEDLINE, Scopus, and NASA Technical Reports Server searched 1990–2025, 82 of 312 records included: spaceflight studies with DXA, QCT, or HR-pQCT, bed-rest RCTs, systematic reviews.Results: ARED reduced hip BMD loss by ~40% versus aerobic-only protocols, proximal femur deficits persist. HR-pQCT confirmed resorption exceeded formation threefold in-flight, bone repair concentrated within 6 months. QCT revealed trabecular deficits at 24 months despite DXA normalisation. Alendronate preserved BMD in the only spaceflight RCT (n=28).Conclusions: Available evidence suggests current exercise countermeasures may be insufficient for missions beyond six months. Bisphosphonate therapy alongside ARED may be considered for high-risk crewmembers, though evidence is limited to a single small trial. Longer missions will likely require multimodal strategies. Pre-flight risk stratification and anti-sclerostin trials are priority research needs.